Evidence for cryptic sulfur cycling in Atlantic ocean sediments affected by aeolian dry deposition of Saharan dust - Grijalva-Rodriguez, Tomas Israel; Turchyn, Alexandra V.; Albin, Sharon; Eliani-Russak, Efrat; Manashirov, Alen; Zweig, Irina; Kamyshny, Alexey (Frontiers in Marine Science, 2025)
Cryptic sulfur cycling, characterized by nearly quantitative oxidation of hydrogen sulfide, is characteristic for sediments with low organic matter and high reactive iron contents. A common source of reactive iron in sediments of marine systems that are located in arid environments is aeolian dry deposition of desert dust. The presence of such a cryptic sulfur cycle has previously been documented in sediments of enclosed basins such as the Red Sea and, especially, in its north-eastern extension, the Gulf of Aqaba. Here we present speciation data for iron, manganese and sulfur as well as the isotopic composition of sulfate, and demonstrate cryptic sulfur cycling in sediments from the north-east Atlantic Ocean situated in the vicinity of the Sahara. These sediments are characterized by high reactive-to-total-iron ratios and extremely low sulfur-bound iron contents. In the near-shore sediments (e.g., sediments which were sampled at < 550 km from the coast) highly reactive iron contents are higher than in the sediments, which were retrieved at higher distances from the continent. In the near-shore sediments, the most abundant highly reactive iron fraction is dithionite-extractable iron, which comprises goethite, hematite, and akaganéite. This is the most abundant group of minerals in the Saharan dust collected above the Red Sea. On the other hand, contents and speciation of highly reactive iron does not significantly affect sedimentary sulfur-bound iron contents. We suggest that cryptic sulfur cycling is a common phenomenon for sediments in the ocean situated near arid environments.